2013
DOI: 10.1021/es403585h
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Cu, Fe, Pb, and Zn Oxides and Chlorides as a Determinant of Chlorinated Aromatics Generation in Municipal Solid Waste Incinerator Fly Ash

Abstract: We investigated chemical determinants of the generation of chlorinated aromatic compounds (aromatic-Cls), such as polychlorinated biphenyls (PCBs) and chlorobenzenes (CBzs), in fly ash from municipal solid waste incineration. The influences of the following on aromatic-Cls formation in model fly ash (MFA) were systematically examined quantitatively and statistically: (i) inorganic chlorides (KCl, NaCl, CaCl2), (ii) base materials (SiO2, Al2O3, CaCO3), (iii) metal oxides (CuO, Fe2O3, PbO, ZnO), (iv) metal chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…Yang et al ( 20 ) reported that the average PM2.5/TPM ratio emitted from a municipal solid waste incinerator was 0.93, and the major chemical species detected in PM2.5 were organic carbon, chloride ions, ammonium ions, elemental carbon, and silicon, while the minor species were sulfate ions, potassium ions, sodium, potassium, nitrate, aluminum, calcium ions, zinc, calcium, copper, iron, lead, and magnesium. Fujimori et al ( 21 ) reported that the chemical determinants of the generation of aromatic-Cl, such as polychlorinated biphenyls (PCBs) and chlorobenzenes, in fly ashes from municipal solid waste incineration were the precise ratios of copper, iron, lead, and zinc chlorides and oxides.…”
Section: Resultsmentioning
confidence: 99%
“…Yang et al ( 20 ) reported that the average PM2.5/TPM ratio emitted from a municipal solid waste incinerator was 0.93, and the major chemical species detected in PM2.5 were organic carbon, chloride ions, ammonium ions, elemental carbon, and silicon, while the minor species were sulfate ions, potassium ions, sodium, potassium, nitrate, aluminum, calcium ions, zinc, calcium, copper, iron, lead, and magnesium. Fujimori et al ( 21 ) reported that the chemical determinants of the generation of aromatic-Cl, such as polychlorinated biphenyls (PCBs) and chlorobenzenes, in fly ashes from municipal solid waste incineration were the precise ratios of copper, iron, lead, and zinc chlorides and oxides.…”
Section: Resultsmentioning
confidence: 99%
“…However, information on the occurrence and emission characteristics of both low and highly chlorinated benzenes is still limited, particularly in ash samples. In addition, the abundance of low-chlorinated benzenes, especially in fly ash generated from municipal waste incineration was also reported in previous studies (Fujimori et al 2010(Fujimori et al , 2014. In geographical point of view, most of the studies on the emission of U-POPs including CBzs from industry have been conducted in China (Liu et al 2009(Liu et al , 2013Nie et al 2011Nie et al , 2012Zhang et al 2011), Taiwan (Chen et al 2007), and Japan (Akimoto et al 1997;Murakami et al 2008;Fujimori et al 2010Fujimori et al , 2014.…”
Section: Introductionmentioning
confidence: 54%
“…26 The amount cannot be determined at present on the Pb L-edge due to the available literature being of insufficient resolution, but if chlorine gas is present, the risk of further reactions contaminating samples must be considered and may make comparisons to previous work difficult. 27 At present, we do not see a simple way around this problem in photoabsorption measurements, as the light itself will induce the formation of chlorine gas. A lower photon flux would mitigate the problem, but one would have to carefully raster a very homogeneous sample in order to solve the problem.…”
Section: Discussionmentioning
confidence: 96%